HAK ATAS PELAYANAN DAN PERLINDUNGAN KESEHATAN IBU DAN ANAK (Implementasi Kebijakan Di Kabupaten Banyumas) - Tedi Sudrajat; Agus Mardianto (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Design of services and health protection for mothers and children in Banyumas directed by a strategic policy to reducing Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR). In its implementation, especially in Maternal Mortality, the policies were still exceeded the target of Millennium Development Goals (MDGs). In the term of legal protection, the policy not mention the sanction and it’s influence the implementation that not optimal. But if there are omissions or errors that indicated malpractice will be subject by criminal, civil, administrative and ethics sanctions. Key words: health service, legal protection, maternal and child health